The study of spherical geometry in Mathematics teacher education: an experience based on the use of manipulable materials (Research, Society and Development, 2021)
The present work addresses the main results of a research, whose focus was to present concepts of Spherical Geometry through manipulable materials and activities oriented to undergraduate students in Mathematics. To give theoretical and conceptual support to the research, we considered parameters of the use of manipulable materials in the teaching of mathematics and the teaching of geometry in Brazil. The methodology used sought to reconcile ideas on the use of manipulable materials for the organization of oriented activities that allowed students to make discoveries for themselves. The activities were applied to students of the Mathematics Degree course of a Federal Institute. The research results were qualitatively analyzed using Van Hiele model parameters to describe the performance of those involved. The contribution of the results of this research is inserted in the context of geometry teaching, specifically in the use of manipulable materials in the teaching-learning process.